Early-life exposure to p, p′-DDT and p, p′-DDE in South African children participating in the VHEMBE study: An assessment using repeated serum measurements and pharmacokinetic modeling. (October 2018) - Verner, Marc-André; Chevrier, Jonathan; Ngueta, Gérard; Rauch, Stephen; Bornman, Riana; Eskenazi, Brenda
Abstract: Background: The World Health Organization recommends indoor residual spraying (IRS) of insecticides (including dichlorodiphenyltrichloroethane [DDT]) to fight malaria vectors in endemic countries. There is limited information on children's exposure to DDT in sprayed areas, and tools to estimate early-life exposure have not been thoroughly evaluated in this context. Objectives: To document serum p, p ′-DDT/E levels in 47 mothers and children participating in the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE), a study conducted in an area where IRS insecticides are used annually, and to evaluate the precision and accuracy of a published pharmacokinetic model for the estimation of children's p, p ′-DDT/E levels. Methods: p, p ′-DDT/E levels were measured in maternal serum at delivery, and in children's serum at 12 and 24 months of age. A pharmacokinetic model of gestational and lactational exposure was used to estimate children's p, p ′-DDT/E levels during pregnancy and the first two years of life, and estimated levels were compared to measured levels. Results: The geometric means of children's serum p, p ′-DDT/E levels at 12 and 24 months were higher than those of maternal serum levels. Regression models of measured children's p, p ′-DDT/E levels vs. levels estimated with the pharmacokinetic model (which only accounted for children's exposure through placental transfer and breastfeeding) had coefficients of determination (R 2 ) ranging from 0.75 to 0.82. Estimated p, p ′-DDE levels were not significantly different from measured levels, whereas p, p ′-DDT levels were overestimated by 36% at 12 months, and 51% at 24 months. Conclusion: Results indicate that children living in a sprayed area have serum p, p ′-DDT/E levels exceeding their mothers' during the first two years of life. The pharmacokinetic model may be useful to estimate children's levels in the VHEMBE population. Highlights: Children's p, p ′-DDT/E levels at 12 and 24 months were higher than maternal levels. The pharmacokinetic model of children's lactational exposure showed good precision. Results suggested breastfeeding is the main contributor to children's exposure. Pharmacokinetic modeling can be used to estimate children's levels in sprayed areas.